Pemberdayaan Pokdarwis dalam Mengembangkan Homestay di Desa Bukit Rawi Kecamatan Kahayan Tengah Kabupaten Pulang Pisau (Neolectura, 2020)
This empowerment aims to provide assistance to members of the Rawi Basewut tourism awareness group in Bukit Rawi Village, Kahayan Tengah District, Pulang Pisau Regency regarding ecotourism management in particular developing the potential for home stay to complement the tourism facilities in the village. This empowerment starts with social analysis and then continues with appreciative inquiry methods, which includes the discover, dream, design, and destination stages and do the PRA (participatory rural appraisal) approach. The target of this empowerment activity is the members of the Rawi Basewut tourism awareness group (pokdarwis) in the village of Bukit Rawi who is actively involved in the management of the tourism village. Tourism awareness groups are given training, socialization, assistance and empowerment regarding ecotourism management. The results of this dedication show excellent motivation from the tourism-conscious group in planning management and developing home stays, through the fulfillment of facilities according to needs, maintenance and promotion in order to empower the economy of the community around tourist attractions.